Efficacy of Papacarie in Reduction Total Bacterial Count in Comparison with the Conventional Rotary Method - Muna H. Al-Swaidy; Ban A. Salih (College of Dentistry/ University of Baghdad, 2016)
Background: The change in the concepts of cavity preparation and the development of reliable adhesive materials lead to the development of alternative methods of caries removal. Chemo-mechanical caries removal (CMCR) involves the chemical softening of carious dentin, followed by its removal with manual excavation. The present study was conducted to evaluate clinically the efficiency of caries removal using a new chemo-mechanical agent (Papacarie) compared to the conventional drilling method in reduction of total bacterial count. Material and methods: The study is a split mouth design. The sample composes from sixty mandibular deciduous molars teeth in thirty children, between six to nine years of age with bilateral class I deep occlusal carious lesions without pulp involvement. Samples of this study were classified into group A and B with thirteen teeth for each. In groupAtreatment by Papacárie while group B were treated by the conventional drilling method Results: The results showed significant different in total bacterial count in period after treatment with Papacarie as comparative with drill method for caries remove. Conclusions: It was concluded that Papacarie could be an effective caries removal method to treat children, particularly those who present with early childhood caries or management problems.